Optimasi Proses Ekstraksi Daun Sirih Hijau (Piper betle L.) yang Memiliki Aktivitas Antioksidan Berdasarkan Penggunaan secara Empiris - Farendina Suarantika; Vinda Maharani Patricia; Hanifa Rahma (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Green betel (Piper betle L.) exhibits various pharmacological activities, including antiallergic, analgesic, antibacterial, antiproliferative, and antioxidant, and contains various chemical compounds such as chavibetol, chavibetol acetate, carvacrol, caryophyllene, allyl pyrocatechol diacetate, campene, chavibetol methyl ether. This research was conducted to optimize green betel leaf processing techniques which were applied empirically by the community, through testing the antioxidant activity using the Ferric Reducing Antioxidant Power (FRAP) method. Processing techniques that are optimized are infusion, fresh brewed, and soaked boiled. The antioxidant activity of fresh brewed green betel leaf extract has an antioxidant capacity of 18.126 mg Trolox/g extract. For green betel leaf extract boiled and soaked, it is 21.848 mg Trolox/g extract, while for infusion green betel leaf extract is 22.809 mg Trolox/gram extract. The highest antioxidant activity was given by green betel leaf infusion extract, 22.809 mg Trolox/gram extract.